“Ipsilateral, high, single-hand, sideways”—Ruijin rule for camera assistant in uniportal video-assisted thoracoscopic surgery - Gao, Taotao; Xiang, Jie; Jin, Runsen; Zhang, Yajie; Wu, Han; Li, Hecheng (Journal of Thoracic Disease, 2016)
Camera assistant plays a very important role in uniportal video-assisted thoracoscopic surgery (VATS), who acts as the eye of the surgeon, providing the VATS team with a stable and clear operating view. Thus, a good assistant should cooperate with surgeon and manipulate the camera expertly, to ensure eye-hand coordination. We have performed more than 100 uniportal VATS in the Department Of Thoracic Surgery in Ruijin Hospital. Based on our experiences, we summarized the method of holding camera, known as “ipsilateral, high, single-hand, sideways”, which largely improves the comfort and fluency of surgery.